2017
DOI: 10.1016/j.livres.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3 in immune response and metabolic regulation

Abstract: Activating transcription factor 3 (ATF3) is a member of the ATF/cAMP-response element binding protein (CREB) family of transcription factors. In response to stress stimuli, ATF3 forms dimers to activate or repress gene expression. Further, ATF3 modulates the immune response, atherogenesis, cell cycle, apoptosis, and glucose homeostasis. Recent studies have shown that ATF3 may also be involved in pathogenesis of other diseases. However, more studies are needed to determine the role of ATF3 in metabolic regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…Previous studies focusing on the role of ATF3 in hepatic steatosis, glucose, and insulin homeostasis came out with contradictory conclusions . Recently, a study published by Kim et al corroborated the fact that ATF3 is the key molecule linking hepatic steatosis and impaired glucose homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on the role of ATF3 in hepatic steatosis, glucose, and insulin homeostasis came out with contradictory conclusions . Recently, a study published by Kim et al corroborated the fact that ATF3 is the key molecule linking hepatic steatosis and impaired glucose homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…has been shown that ATF3 is rapidly induced by a wide range of challenges such as DNA damage, oxidative and ER stress (9,10), leading to the activation of signaling pathways required for the maintenance of cellular homeostasis (8,11). ATF3 is known to activate and repress transcription through its binding to the canonical cis-regulatory element 5'-TGACGTCA-3' via its basic region-leucine zipper domain as an homodimer or heterodimer, in combination with other ATFs or AP-1 transcription factors (12). Despite the evidence linking ATF3 to cellular stressors, there is currently no data on whether ATF3 levels are regulated by stimuli such as cold or -adrenergic signaling in adipose depots.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the translocases of the outer mitochondrial membrane (OMM), TOMM22 and TOMM70, were differentially phosphorylated at multiple sites which is thought to regulate mitochondrial protein import (Matic et al, 2018;Schmidt et al, 2011). The down-modulation of ATF3 is a bZIP domain transcription factor implicated in multiple cellular stress responses that can either activate or repress transcription of its target genes (Jadhav and Zhang, 2017). Interestingly, ATF3 has been recently discussed as one of the putative mammalian homologues of ATFS-1, the central UPR mt regulator in C.elegans (Münch and Harper, 2016).…”
Section: Lp Reshapes the Mitochondrial Proteomementioning
confidence: 99%